Verba Mencuci “Kumbah” dalam Bahasa Jawa: Kajian Metabahasa Semantik Alami - Khoirul Huda, Muhammad; Nikmatullah, Miftahula Rizqin; Nurahmah, Nusaiba; Herpindo (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Javanese is a language used in the daily lives of people who pay attention to the norms in speaking. But unfortunately, the use of Javanese language has begun to fade, which can be proven by the neglect of the use of Javanese language in conversation, and not a few people also do not know Javanese language, including verbs. There are many verbs in the Javanese language, but the researcher wants to focus on the verb washing